Pengaruh Pemasaran Digital dan E-Commerce terhadap Performance Marketing dan Keberlanjutan Bisnis Pada Usaha Oleh-Oleh Khas Kota Solo - Wardana, Firdaus Putra; Mukharomah, Wafiatun (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to analyze digital marketing and e- ecommerce on performance marketing and business sustainability in the typical souvenir business of Solo city. The population and sample of this study are SMEs who have a business in the field of souvenirs typical of Solo City as many as 100 respondents. The type of data used in this study is primary data. Data collection methods using questionnaires and processed using Partial Least Square (PLS) analysis tools. The results showed that E-commerce has a positive effect on business sustainability, digital marketing has a positive effect on business sustainability, performance marketing has a positive effect on business sustainability, E-commerce has a positive effect on performance marketing, digital marketing has a positive effect on performance marketing, performance marketing mediates the effect of E-commerce on business sustainability, performance marketing mediates the effect of digital marketing on business sustainability.